A Comprehensive Understanding of the Use of e-Learning in Continuing Education: Experiences of Pharmacists in a Public Health System - Andrigo Antonio Lorenzoni PhD candidate; Fabiola Bagatini Buendgens PhD; Fernanda Manzini PhD; Norberto Rech PhD; Silvana Nair Leite Professor (SAGE Publishing, 2021)
Introduction: The health and education sectors have experienced rapid technological development. In this scenario, the use of Internet technology has grown as an option for the expansion of continuing education (CE), as it allows professionals to develop educational activities with flexibility, autonomy, and convenience. E-learning has gained popularity and currently, thousands of online courses are being offered. However, studies of e-learning in professional training have presented only a few specific foci of study. Objective: to develop a comprehensive approach to understand both the experience and the complex scenario of the use of e-learning in the CE for pharmacists. Method: Field research in 10 Brazilian states through interviews and focus groups with alumni of a CE e-learning specialization course for pharmacists in public health. Data analysis used the model of socio-technical systems and was based on a framework with the components Objectives, People, Processes, Culture, Technology, Infrastructure, and Scenario. Results: The People and Culture components indicated the assimilation and normalization of technologies in the educational process. Although the infrastructure (technical and organizational) was deficient in some regions, the Technology component suggested that the characteristics of the course design, associated with the personal characteristics of the students, provided ways to overcome obstacles. The objectives of the use of distance education seem to be related to the possibility of greater accessibility and autonomy. The Processes component, in turn, revealed the burden that a e-learning course puts on the pharmacist. Conclusion: E-learning proved to be useful to enable and expand access to education, providing pharmacists with an opportunity for CE. On the other hand, e-learning contributes to the normalization of the precarious working conditions of pharmacists, attributing to individuals the sole responsibility for the CE even in an institutional CE program, which results in work overload.